1999
DOI: 10.1161/01.cir.99.10.1385
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Linking T-Wave Alternans to the Genesis of Cardiac Fibrillation

Abstract: Background-Although T-wave alternans has been closely associated with vulnerability to ventricular arrhythmias, the cellular processes underlying T-wave alternans and their role, if any, in the mechanism of reentry remain unclear. Methods and Results-T-wave alternans on the surface ECG was elicited in 8 Langendorff-perfused guinea pig hearts during fixed-rate pacing while action potentials were recorded simultaneously from 128 epicardial sites with voltage-sensitive dyes. Alternans of the repolarization phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
865
6
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(909 citation statements)
references
References 42 publications
36
865
6
2
Order By: Relevance
“…The number of nodes seen depended partially on tissue length. Although only single nodes have been observed experimentally, 8 this study predicts that more may be found if larger tissues are studied. Simulations also successfully replicated the experimental observation of faster pacing converting concordant to discordant alternans.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The number of nodes seen depended partially on tissue length. Although only single nodes have been observed experimentally, 8 this study predicts that more may be found if larger tissues are studied. Simulations also successfully replicated the experimental observation of faster pacing converting concordant to discordant alternans.…”
Section: Discussionmentioning
confidence: 80%
“…Alternatively, conduction block occurring every other beat resulting in alternating conduction patterns and alternating size of excited tissue also could produce TWA. 7 A recent optical mapping study by Pastore et al 8 elegantly demonstrated a relationship between discordant alternans associated with TWA and arrhythmia induction. Discordant alternans is the phenomenon of two spatially distinct regions exhibiting APD alternans of opposite phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AP alternans in amplitude and duration are frequently observed at the onset of ischemia (21,45) and during rapid pacing (15,48). It was demonstrated that elevation of [K ϩ ] o can also cause AP alternans (19,38).…”
Section: Discussionmentioning
confidence: 99%
“…Because heart cells are refractory to further stimulation during an action potential, alternans of APD results in an alternans of refractoriness, the magnitude of which may vary across different regions of the heart. Several studies have shown that the resulting spatial dispersion of refractoriness facilitates the development of local conduction block [2][3][4][5], which may in turn cause the normally planar wave of electrical excitation in cardiac tissue to break and form spiral waves [6]. If the spiral waves also encounter regions of disparate refractoriness, they may disintegrate into multiple wavelets, which may account for the onset of the lethal heart rhythm disorder ventricular fibrillation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%